2016
DOI: 10.1039/c6ra16892b
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature volatile organic compounds sensing based on WO3·0.33H2O, hexagonal-WO3, and their reduced graphene oxide composites

Abstract: The sensors based on WO3·0.33H2O, RGO-WO3·0.33H2O, h-WO3, and RGO-h-WO3 showed great VOCs sensing properties at room temperature and 55% relative humidity. The materials exhibited a p-type behavior. RGO improved the acetone sensing response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 55 publications
1
26
1
Order By: Relevance
“…This crystalline structure is identical to hydrated tungsten oxide WO 3 -H 2 O of orthorhombic structure. This type of structure was also observed in the case of hydrothermal and solvothermal synthesis of tungsten oxide nanoparticles for sensing volatile organic compound (Perfecto et al, 2016) and photocatalytic activity (Liu et al, 2019), respectively. The calcination of WO 3 -H 2 O at 200 and 600°C respectively showed different XRD patterns.…”
Section: Catalytic Testssupporting
confidence: 55%
“…This crystalline structure is identical to hydrated tungsten oxide WO 3 -H 2 O of orthorhombic structure. This type of structure was also observed in the case of hydrothermal and solvothermal synthesis of tungsten oxide nanoparticles for sensing volatile organic compound (Perfecto et al, 2016) and photocatalytic activity (Liu et al, 2019), respectively. The calcination of WO 3 -H 2 O at 200 and 600°C respectively showed different XRD patterns.…”
Section: Catalytic Testssupporting
confidence: 55%
“…The second article was about the engineering of tungsten trioxide/reduced graphene oxide-based materials, which was again very promising for the acetone detection at 22 °C and RH of 55%. Specifically, as already unraveled in a previously cited paper, Perfecto et al [ 95 ] successfully synthesized RGO-h-WO 3 ⋅0.33H 2 O (hexagonal WO 3 polymorph) by the one-pot microwave-assisted hydrothermal method. The authors found that all the materials behave as p-type semiconductors after being exposed to reducing gases, evidencing a 20% greater response for the composite material with respect to pure WO 3 ( Figure 8 k).…”
Section: Reduced Graphene Oxide-based Chemoresistorsmentioning
confidence: 98%
“…Moreover, it can detect the acetone even at sub-ppm concentration (~0.2 ppm) and the sensor can operates at 90% humid condition, thus become an exceptional candidate in acetone quantitation. Apart from the aforementioned diverse nanostructures, nanocomposites that are not described under any unique nano-architectures also show their high selective sensitivity to acetone [148][149][150][151][152][153] as shown in Table 1. Wherein, a few of them operate at diverse humid conditions (10-90% RH) and some others require optimization of operating temperature to attain high sensitivity.…”
Section: Diverse Nanostructures In Acetone Detectionmentioning
confidence: 99%